2020
DOI: 10.3389/fonc.2020.01723
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of EBV-Related Lymphoproliferative Disease in HIV-Positive Individuals

Abstract: Epstein-Bar virus (EBV) can directly cause lymphoproliferative disease (LPD), including AIDS-defining lymphomas such as Burkitt's lymphoma and other non-Hodgkin lymphomas (NHL), as well as human immunodeficiency virus (HIV)-related Hodgkin lymphoma (HL). The prevalence of EBV in HL and NHL is elevated in HIV-positive individuals compared with the general population. Rates of incidence of AIDS-defining cancers have been declining in HIV-infected individuals since initiation of combination anti-retroviral therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 215 publications
2
50
0
1
Order By: Relevance
“…For instance, EBV-associated posttransplant lymphoproliferative disorders (PTLDs) usually express all the latent genes, known as the latency III program, that encode six nuclear (EBNA1, -2, -3A, -3B, -3C, and -LP) and three membrane (LMP1, -2A, and -2B) antigens, along with untranslated RNAs [ 48 ]. HL express a pattern, characterized by the expression of EBNA1 and LMP1 and LMP2 antigens, identified as latency II [ 49 ], while BL displays latency I pattern, that predominantly expresses EBNA1 [ 48 ] ( Table 2 ). In all latency types, infected cells express two EBV-encoded small RNAs, known as EBER-1, and EBER-2 [ 48 ].…”
Section: Ebv Latent and Lytic Antigen Expressionmentioning
confidence: 99%
“…For instance, EBV-associated posttransplant lymphoproliferative disorders (PTLDs) usually express all the latent genes, known as the latency III program, that encode six nuclear (EBNA1, -2, -3A, -3B, -3C, and -LP) and three membrane (LMP1, -2A, and -2B) antigens, along with untranslated RNAs [ 48 ]. HL express a pattern, characterized by the expression of EBNA1 and LMP1 and LMP2 antigens, identified as latency II [ 49 ], while BL displays latency I pattern, that predominantly expresses EBNA1 [ 48 ] ( Table 2 ). In all latency types, infected cells express two EBV-encoded small RNAs, known as EBER-1, and EBER-2 [ 48 ].…”
Section: Ebv Latent and Lytic Antigen Expressionmentioning
confidence: 99%
“…Presently, cancer remains one of the most serious threats facing PLHW, and lymphomas are the most common cause of PLWH death in developed nations [ 75 ]. EBV is still responsible for more than half of the cases of lymphomas arising in these individuals [ 76 ]. For instance, Simard et al reported that, while the burden of AIDS-defining cancers decreased from 18% to 4.2% with ART, the risk of classical Hodgkin lymphoma (cHL) increased [ 77 ], and EBV remains responsible for close to 100% of all cHL cases [ 78 ].…”
Section: Hiv Steady B Cell Stimulation Creates a Lymphomagenesis Permissive Environmentmentioning
confidence: 99%
“…EBV establishes a latent infection in over 90% of human adults, alternating between episodes of latency and reactivation inside B-lymphocytes, which may lead to the malignant transformation of B cells. Thus, EBV has been linked to a broad spectrum of human malignancies [ 55 ]. Additionally, EBV coinfection may alter HIV-infected patients' immunological response, increasing inflammation and immune activation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EBV has been linked to a broad spectrum of human malignancies [ 55 ]. Additionally, EBV coinfection may alter HIV-infected patients' immunological response, increasing inflammation and immune activation [ 55 ]. However, these SDE genes deregulated in the EBV pathway are also involved in many other immune pathways that may have been affected after HCV treatment.…”
Section: Discussionmentioning
confidence: 99%